Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.nanolett.6b04218
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of Ceria Nanoarrays on Anatase Titania Powder: A Bottom-up Physical Picture

Abstract: The leading edge of catalysis research motivates physical understanding of the growth of nanoscale oxide structures on different supporting oxide materials that are themselves also nanostructured. This research opens up for consideration a diverse range of facets on the support material, versus the single facet typically involved in wide-area growth of thin films. Here, we study the growth of ceria nanoarchitectures on practical anatase titania powders as a showcase inspired by recent experiments. Density func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Therefore, to evaluate the formation of rh-In 2 O 3 structure at low processing temperatures and phase transition from a rhombohedral to cubic structure, the growth mechanism of initial In 2 O 3 layers onto substrate was studied using DFT calculations. First, in our previous report on the epitaxial growth of CeO 2 (001) on anatase–TiO 2 (112), we found that cubic-fluoride CeO 2 (001) layers can be directly grown on the anatase–TiO 2 (112) surface without any buffer layers because of the morphological similarity in the surface structural motifs of TiO 2 (112) and CeO 2 (001) . On the other hand, because SiO 2 and In 2 O 3 differ in their crystal structures and protruding SiO x units from the SiO 2 (001) surface (see Figure a) hinder the direct growth of In 2 O 3 crystals on SiO 2 (001), initial buffer layers of In 2 O 3 were built by repeatedly depositing indium and oxygen atoms on SiO 2 (001) and the combined In 2 O 3 /SiO 2 (001) was used as a basement layer for subsequent DFT calculations of In 2 O 3 growth (Figure a–c).…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, to evaluate the formation of rh-In 2 O 3 structure at low processing temperatures and phase transition from a rhombohedral to cubic structure, the growth mechanism of initial In 2 O 3 layers onto substrate was studied using DFT calculations. First, in our previous report on the epitaxial growth of CeO 2 (001) on anatase–TiO 2 (112), we found that cubic-fluoride CeO 2 (001) layers can be directly grown on the anatase–TiO 2 (112) surface without any buffer layers because of the morphological similarity in the surface structural motifs of TiO 2 (112) and CeO 2 (001) . On the other hand, because SiO 2 and In 2 O 3 differ in their crystal structures and protruding SiO x units from the SiO 2 (001) surface (see Figure a) hinder the direct growth of In 2 O 3 crystals on SiO 2 (001), initial buffer layers of In 2 O 3 were built by repeatedly depositing indium and oxygen atoms on SiO 2 (001) and the combined In 2 O 3 /SiO 2 (001) was used as a basement layer for subsequent DFT calculations of In 2 O 3 growth (Figure a–c).…”
Section: Resultsmentioning
confidence: 96%
“…56 To treat the highly localized Ce 4f orbital, DFT + U 57 with U eff = 4.5 eV was applied. 58,59 The interaction between the ionic cores and the valence electrons was described using the projector-augmented wave method. 60 Valence electron functions were extended with the planewave basis to an energy cutoff of 400 eV.…”
Section: Introductionmentioning
confidence: 99%
“…We performed spin-polarized DFT calculations with the Vienna ab initio simulation package (VASP) and the PW91 functional. To treat the highly localized Ce 4f orbital, DFT+U with U eff = 4.5 eV , was applied. The interaction between the ionic cores and the valence electrons was described by the projector-augmented wave method .…”
Section: Computational Detailsmentioning
confidence: 99%